2016
DOI: 10.1016/j.neuroimage.2015.08.079
|View full text |Cite
|
Sign up to set email alerts
|

STEAM — Statistical Template Estimation for Abnormality Mapping: A personalized DTI analysis technique with applications to the screening of preterm infants

Abstract: We introduce the STEAM DTI analysis engine: a whole brain voxel-based analysis technique for the examination of diffusion tensor images (DTIs). Our STEAM analysis technique consists of two parts. First, we introduce a collection of statistical templates that represent the distribution of DTIs for a normative population. These templates include various diffusion measures from the full tensor, to fractional anisotropy, to 12 other tensor features. Second, we propose a voxel-based analysis (VBA) pipeline that is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 65 publications
0
23
0
Order By: Relevance
“…A whole‐brain voxel‐based analysis found a greater extent of abnormalities on mean diffusivity, axial diffusivity, and radial diffusivity in infants with poorer motor outcome compared with infants with normal motor outcomes . Tract‐based spatial statistics applied to MRI acquired at PMA of 30 to 33 weeks found that infants with poorer motor outcomes had lower axial diffusivity and radial diffusivity in the corpus callosum, and internal and external capsule (but no association with fractional anisotropy) .…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…A whole‐brain voxel‐based analysis found a greater extent of abnormalities on mean diffusivity, axial diffusivity, and radial diffusivity in infants with poorer motor outcome compared with infants with normal motor outcomes . Tract‐based spatial statistics applied to MRI acquired at PMA of 30 to 33 weeks found that infants with poorer motor outcomes had lower axial diffusivity and radial diffusivity in the corpus callosum, and internal and external capsule (but no association with fractional anisotropy) .…”
Section: Resultsmentioning
confidence: 95%
“…S1, online supporting information). Twenty‐six studies met the inclusion criteria and five further studies were identified by manual review of references of included papers . Demographic and clinical data extracted from the 31 studies included in this review are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations